Development of simple design-oriented procedure for predicting the collision damage of FPSO caisson protection structures. (15th September 2017) - Cho, Sang-Rai; Le, Dinh Ngoc Can; Jeong, Jang-Hyun; Frieze, Paul A.; Shin, Hyun-Kyoung
Abstract: Protection structures for FPSO (Floating Production Storage and Offloading) caissons should be sufficiently strong so as not to contact caisson pipes even when the protection structure is damaged by an impact by attendant vessels. In the present structural design process, non-linear commercial packages are employed for collision analyses. However, non-linear collision analyses using commercial packages are time-consuming and expensive to operate, especially in the initial design stage. In this study, substantiation of the adopted commercial package was first performed using collision test results on single pipes and H-shape pipes. Then, a rigorous parametric study was conducted by changing the design variables. A simple analytical expression was derived assuming that the kinetic energy of the striking vessel was dissipated by the plastic elongation of pipes and rotation of plastic hinges. Using the parametric study results, design equations to predict the maximum deflection and overall bending damage were obtained by which the effects of local denting and dynamic behaviour could be considered. Additionally, an equation to predict the extent of local denting damage was also derived. The developed procedure was numerically substantiated using the predicted extent of damage to an actual protection structure. Highlights: Collision damage of FPSO caisson protection structures is developed in this study. Numerical analysis method was substantiated using the collision tests results. Simple design equations were derived using the parametric study results. Maximum deflection, maximum overall bending and local denting damage are predicted. A calculation example is also provided for the developed procedure.